G236(P) Acute kidney injury secondary to acute bilateral vesicoureteric obstruction: a case report. (May 2019) - Lee, AM; Martin, N; De, S
Abstract : We present an unusual case of a previously fit and well 2 and a half year old boy who suffered acute kidney injury (AKI) secondary to bilateral renal obstruction during an episode of acute illness. He presented to his local DGH with a febrile lower respiratory tract illness and was treated with intravenous antibiotics. He subsequently developed persistent vomiting, without abdominal pains, leading to dehydration. He became anuric with a rapid rise in serum creatinine despite intravenous rehydration and furosemide. He was transferred to a specialist unit for further paediatric nephrology care. Results: His presenting creatinine was 300 umol/L (15–31 umol/L), urea 10.9 mmol/L (2.9–7.5 mmol/L), haemoglobin 123 g/L (115–135 g/L) and platelets 517 × 109/L (150–450 × 109/L). An anti-glomerular basement membrane quickcard test was negative, Antistreptolysin O titres, C3 and C4 complement levels were normal. A renal ultrasound showed bilateral pelvicalyceal and ureteric dilatation, with patent renal veins and arteries. A urinary metabolic screen revealed an elevated urine calcium:creatinine ratio (1.14 mmol/mmol)and urinary oxalate:creatinine ratio of 169µmol/mmol. The former subsequently fell to within the normal range. The debris described below was sent for analysis but no major component was identified. Further management: A cystoscopy showed calcific debris at the vesicoureteric junctions bilaterally. A saline washout resulted in immediate production of urine from both ureters. Bilateral JJ stents were inserted. In the post-operative period, the anuria resolved and the creatinine continued to fall. He had significant post-obstructive diuresis which settled prior to discharge. The serum creatinine normalised to 17 umol/L. He was discharged on oral potassium citrate. Repeat renal ultrasound scan showed normal kidneys with no hydronephrosis, renal scarring or residual calculi. Conclusion: This was an unusual presentation of bilateral renal obstruction during an episode of acute illness. To our knowledge, this has yet to be described in the literature. Urolithiasis is rare in children, particularly in the absence of evidence of predisposing conditions like urinary infections, genetic diseases, tubular disorders or congenital renal tract anomalies. Prompt diagnosis and intervention is paramount to prevent further progression of AKI. It remains uncertain if this may recur with future episodes of acute illness. He remains under nephrology follow-up.